Modal Sosial dalam Perspektif Al-Qur’an: Analisis Konsep Ukhuwah sebagai Fondasi Kepercayaan dan Jaringan Ekonomi - Iqlima Khoirunnisa; Puji Ayuni Anawawi; Lina Marlina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the concept of ukhuwah (brotherhood) from the perspective of the Qur’an as the foundation of social capital in Islam. Social capital in modern social theory is understood as networks, norms, and trust that strengthen collaboration between individuals and groups. In Islam, the spiritual foundation has been embedded through the value of ukhuwah. This research uses the library method with a thematic exegesis (mawdhu’i) approach to analyze the Qur’anic verses related to ukhuwah and link them to modern social capital theory. The findings show that ukhuwah plays an important role in cultivating trust (trust capital), strengthening socio-economic networks (network capital), and promoting fair economic distribution. Therefore, ukhuwah serves as a conceptual foundation for Islamic social capital, which is not only relevant in facing contemporary economic challenges but also supports equitable and sustainable economic development for the community. This study provides an understanding that Islamic social capital, built through ukhuwah, can be a solution for creating social justice and sustainable prosperity in society.